Analysis Of The Influence Of Noise On Employee Workload With Ergonomic Approach At Pt. Ciomas Adisatwa Unit Maros - Aliah Alfiah Aras; Nur Ihwan Safutra; Andi Pawennari (Journal of Industrial System Engineering and Management, 2023)
This study aims to determine the effect of noise levels on employee workload with an ergonomic approach at PT. Ciomas Adisatwa Maros Unit. In this study, the determination of the sample taken was 15 people who worked in shift 1 in the factory area. The research method used a quantitative method and a qualitative method. The results of this study found that there was a positive and significant effect between noise level and workload of 0.74. For the significance of the correlation coefficient with an error rate of 5%, and with dk 79, t table = 1.99085 is obtained. It turns out that the calculated t value is greater than the t table price, so Ho is rejected. This means that there is a positive and significant effect of noise level on workload.